FloripaSat-2: An Open-Source Platform for CubeSats - Marcelino, Gabriel Mariano; De Mattos, Andre Martins Pio; Barcellos, Joao Claudio Elsen; Ribeiro, Brenda Fernandes; Seman, Laio Oriel; Filho, Edemar Morsch [UNESP]; Bezerra, Eduardo Augusto (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This letter presents the FloripaSat-2 platform, an open-source service platform already on its second version, including, but not limited to, onboard data handling (OBDH), telemetry, tracking and command (TTC), and electrical power system (EPS) modules. The platform is conceived to be general purpose, i.e., easily adaptable for missions with different payloads and requirements. In this context, an overview of the generic nanosatellite architecture, along with the ongoing missions in which it is being employed, is discussed, including the embedded systems, functionalities, and components. Also, the relevant source code is available in an online repository and can be used and expanded to different kinds of CubeSat missions. Finally, good practices regarding the development and a FlatSat proposal for faster testing of the subsystems are presented to aid engineers in testing and adapting the systems to their mission requirements.
Keywords: CubeSat; nanosatellite; open-source; service platform